Documents diplomatiques : affaires de Mascate : commerce des armes à Mascate, 1912-1914 (LLMC-digital (Series), 1914)
Chiefly correspondence with the British Foreign Office relative to the Sultan's edict of June 4, 1912, respecting the trade in arms and ammunition.